2011
DOI: 10.1176/ps.62.5.pss6205_0525
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Factors Related to Outcome Differences Between Black and White Patients at CMHCs

Abstract: Objectives Data are limited on how clinicians contribute to outcome differences between black patients and white patients. Because the clinician-patient relationship is the foundation of mental health services, understanding clinicians’ role in outcome differences may help identify evidence-based interventions that decrease disparities and capitalize on positive differences. Symptoms and functioning in a sample of black and white adults receiving outpatient services were examined to determine the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Additionally, Hayes et al (2014) replicated these findings in a study of 36 therapists and 228 clients at a university training clinic; however, they examined racial/ethnic disparities in client-reported changes in psychological distress (i.e., Outcome Questionnaire-45; Lambert et al, 1996) as a result of treatment. Larrison et al (2011) also replicated these results in a community mental health sample of 551 clients and 62 therapists. They found that approximately 20% of therapists had better treatment outcomes (i.e., reduction in psychological distress based on the Behavioral and Symptom Identification Scale-24; Eisen, Dill, & Grob, 1994) with their White clients as compared to their Black clients.…”
Section: Therapist Effects In Psychotherapysupporting
confidence: 53%
See 1 more Smart Citation
“…Additionally, Hayes et al (2014) replicated these findings in a study of 36 therapists and 228 clients at a university training clinic; however, they examined racial/ethnic disparities in client-reported changes in psychological distress (i.e., Outcome Questionnaire-45; Lambert et al, 1996) as a result of treatment. Larrison et al (2011) also replicated these results in a community mental health sample of 551 clients and 62 therapists. They found that approximately 20% of therapists had better treatment outcomes (i.e., reduction in psychological distress based on the Behavioral and Symptom Identification Scale-24; Eisen, Dill, & Grob, 1994) with their White clients as compared to their Black clients.…”
Section: Therapist Effects In Psychotherapysupporting
confidence: 53%
“…Building upon this literature, researchers have also found therapists to be one of the primary sources of racial/ethnic disparities in mental health treatment outcomes (Hayes, Owen, & Bieschke, 2014;Imel et al, 2011;Larrison, Schoppelrey, Hack-Ritzo, & Korr, 2011;Owen, Imel, Adelson, & Rodolfa, 2012). That is, racial/ethnic disparities emerge primarily when the differential outcomes between REM and White clients within therapist caseloads are examined.…”
Section: Therapist Effects In Psychotherapymentioning
confidence: 99%
“…Clinicians are one of the primary sources of racial/ethnic disparities in mental health treatment outcome (Hayes, Owen, & Bieschke, 2015;Imel et al, 2011;Larrison, Schoppelrey, Hack-Ritzo, & Korr, 2011;Owen, Imel, Adelson, & Rodolfa, 2012). Owen et al (2015) argue that racial/ethnic disparities emerge mainly when differential outcomes between CALD and mainstream clients within therapist caseloads are examined.…”
Section: Cultural Competence In Practicementioning
confidence: 99%
“…Audio recordings of consumer-provider encounters for depression treatment found that providers engaged in less rapport building communication with black consumers and, despite no differences in patient symptomatology levels, providers were less likely to perceive black consumers as experiencing significant emotional distress [25]. Studies of mental health providers have documented inconsistent treatment outcomes between black and white consumers based on provider cultural competence [26, 27]. Researchers have attempted to address this issue by identifying provider behaviors that contributes to disparities [28], as well as cataloging culturally unique interaction patterns and communication behaviors to inform culturally sensitive care [29, 30].…”
Section: Introductionmentioning
confidence: 99%